ETHICS IN ACCOUNTING PRACTICES AND ITS INFLUENCE ON BUSINESS PERFORMANCE - Nambukara-Gamage, Bandula; Rahman, Samena (PEOPLE: International Journal of Social Sciences, 2020)
The objective of this study is to investigate and identify the importance of ethics in accounting practices and whether ethical accounting practices has any influence on the overall business performance and to create a guideline to encourage accounting professionals to understand and adopt ethical practices. The study explores how various demographical variables, specifically focusing on culture, gender and religion influence on an individual’s ethical decision-making process. The data used in this study was collected from the relevant literatures. The portals’ filters were used to identify the relevant literature to the research. The sample was chosen based upon the four themes including influence of ethical accounting practices on culture, gender, religion and impact on overall business performance. This study revealed that culture does not necessarily influence on ethical behaviour and decision-making. Conversely, a positive correlation has been found between the religion beliefs and ethical decision-making process. However, this research does not clearly point out the influence of ethical accounting practices and its influence on the business performance. This research also highlighted partial connections between how unethical accounting practices and fraudulent activities can become a threat to the business existence. The sample size and research technique restrict the results from generalising.